PENGARUH DEBIT DAN HEAD TERHADAP DAYA MIKRO HIDRO PADA INSTALASI PENGOLAHAN AIR (IPA) PAPALOANG PULAU BACAN - Tri Suyono; Lita Asyriati Latif; Kifli Umar; Fitra Putra Siko (Journal of Science and Engineering, 2018)
Sustainable water resources management system is a water resources management system that is designed and managed and fully contributes to the community (social and economic) for present and in the future, while maintaining the sustainability of its ecological aspects.This research was under taken by direct observation in the field. Then the data obtained from the field is processed using a computer program. This research activity was carried out in Wasile Timur Village, East Halmahera Regency, North Maluku Province. The results of this study indicate that the diameter of the pipe used is diameter 300 mm, 250 mm, 200 mm, 150 mm, 100 mm, and 63 mm. Based on the variation of the pipe, the maximum pressure is 49.37 m or equal to 4.937 bar while the minimum pressure is 26.39 m or equal to 2.639 bar. As for, the pressure from the results of the analysis meets the distribution network planning criteria, namely a maximum of 9.0 - 12.4 bar and a minimum of 0.5 - 1.0 bar. Maximum flow speed of 0.60 m / s and minimum speed of 0.30 m / sec flow velocity. Analysis results is showed the planning criteria which according to the provisions is a maximum of 2.5 m / sec and a minimum of 0.25 m / sec.